IMPROVING TAPIN KAOLIN QUALITY FOR WHITE WARE CERAMIC - Subari Subari; Tatang Wahyudi (Puslitbang tekMIRA, 2014)
Tapin kaolin cannot directly be utilized as raw material for white ware ceramics due to its high Fe2O3 content. It needs upgrading its quality in terms of fulfilling the specification of white ware ceramics. Such the material requires a series of process including washing, wet sieving in magnetic ferro-filter equipment and then dissolv- ing by H2SO4 10%. Based on several parameters such as Al2O3, SiO2 and Fe2O3 contents, 2-µm particle size density, whiteness and plasticity; Tapin kaolin quality develops significantly. XRD analysis shows that the mate- rial does not have maghemite anymore. Quartz is relatively low and mafic minerals are unavailable. Referring to such quality, Tapin kaolin can be used for Parian porcelain.